Is the small heat shock protein HspB1 (Hsp27) a real and predominant target of methylglyoxal modification? - Sudnitsyna, Maria V. (Cell Stress Chaperones, 2019)
This study analyzed the interaction of commercial monoclonal anti-methylglyoxal antibodies that predominantly recognize argpyrimidine with unmodified and modified model proteins and small heat shock proteins. These antibodies specifically recognize methylglyoxal (MG)-modified bovine serum albumin and lysozyme, but they react equally well with both unmodified and MG-modified HspB1. Mutation R188W decreased the interaction of these antibodies with unmodified HspB1, thus indicating that this residue participates in the formation of antigenic determinant. However, these antibodies did not recognize either short (ESRAQ) or long (IPVTFESRAQLGGP) peptides with primary structure identical to that at Arg188 of HspB1. Neither of the peptides obtained after the cleavage of HspB1 at Met or Cys residues were recognized by anti-argpyrimidine antibodies. This means that unmodified HspB1 contains a discontinuous epitope that includes the sequence around Arg188 and that this epitope is recognized by anti-argpyrimidine antibodies in unmodified HspB1. Incubation of HspB1 with MG is accompanied by the accumulation of hydroimidazolones, but not argpyrimidines. Therefore, conclusions based on utilization of anti-argpyrimidine antibodies and indicating that HspB1 is the predominant and preferential target of MG modification in the cell require revision. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12192-019-00975-3) contains supplementary material, which is available to authorized users.